Pengaruh Kualitas Sumber Daya Manusia, Sistem Pengendalian Internal, dan Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (Sakti) Terhadap Penyerapan Anggaran dengan Komitmen Organisasi Sebagai Variabel Moderasi pada Organisasi Perangkat Daerah (OPD - Verawaty Purba; Erlina Erlina; Abdillah Arif Nasution (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Low budget absorption is an important problem that must be faced by various regions in Indonesia, both at the provincial and district/municipality levels. This is caused by several factors ranging from complex bureaucracy, lack of coordination between agencies, limited human resource capacity, inadequate planning, internal control systems, minimal human resource capacity in the use of information technology and low organizational commitment so that this study aims to examine the effect of human resource quality, internal control systems and SAKTI implementation on budget absorption with organizational commitment as a moderating variable in the Regional Apparatus Organization (OPD) of Binjai City. This study uses an empirical (quantitative) approach with a data collection method by survey through an online questionnaire via Google Form. The population in the study includes all employees working in the Regional Apparatus Organization (OPD) of Binjai City, the research sample amounted to 221 respondents selected using purposive sampling techniques, namely samples selected based on certain criteria, in this study the sample was selected who worked in regional financial management. The research data were analyzed and tested using statistical methods including descriptive statistics, classical assumption testing and PLS-SEM analysis, testing was carried out with the help of SPSS and SmartPLS software. The results of the study indicate that human resource quality and SAKTI implementation have a positive and significant effect on budget absorption in Regional Apparatus Organizations (OPD) in Binjai City. The Internal Control System does not significantly influence budget absorption in Regional Apparatus Organizations (OPD) in Binjai City, and Organizational Commitment cannot moderate the effects of human resource quality, internal control systems, and SAKTI implementation on budget absorption in Regional Apparatus Organizations (OPD) in Binjai City.